2020
DOI: 10.3390/en13123096
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life Assessment for Power Cables in Floating Offshore Wind Turbines

Abstract: In this paper, a procedure is proposed to determine the fatigue life of the electrical cable connected to a 5 MW floating offshore wind turbine, supported by a spar-buoy at a water depth of 320 m, by using a numerical approach that takes into account site-specific wave and wind characteristics. The effect of the intensity and the simultaneous actions of waves and wind are investigated and the outcomes for specific cable configurations are shown. Finally, the fatigue life of the cable is evaluated. All analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Fretting and wear damages to the conductors' wires, caused primarily by cyclic bending loads, have been recognized as a challenge for marine cables with metallic armor [18][19][20][21][22][23]. The current study showed that this is also challenging for marine cables without metallic armor.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Fretting and wear damages to the conductors' wires, caused primarily by cyclic bending loads, have been recognized as a challenge for marine cables with metallic armor [18][19][20][21][22][23]. The current study showed that this is also challenging for marine cables without metallic armor.…”
Section: Discussionmentioning
confidence: 65%
“…They also provide mechanical properties that reduce the risk of structural integrity degradation if appropriately designed, such as fatigue, fretting, and wear caused by cyclic loading conditions from the cable's motions. Many studies in the literature have presented results from numerical simulations and experiments of armored dynamic power cables [18][19][20][21][22][23]. Most of them emphasized bending-induced loading conditions and fatigue experiments since this loading mode causes wear and fretting damage to the cable's parts and components.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging the advantage that finite element simulation can substitute the high cost of experiments, the finite element method proves instrumental in enhancing the efficiency of cable optimization, especially in fatigue life calculations [ 25 ]. Suh et al investigated the impact of stress amplitude and average stress on the fatigue life of multi-strand cables under axial loading using FE-safe fatigue analysis software [ 26 ]. Finite element simulation is a numerical method based on mathematical modeling that has become a powerful tool for predicting the fatigue life of structural systems [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the number of research studies focusing on the dynamic response of the FOWTs, the number of publications dedicated to the design and analysis of dynamic power cables is relatively limited. Sobhaniasl et al [36] focused on evaluating the fatigue life of dynamic inter-array power cables for FOWTs. They proposed a comprehensive methodology that accounts for the complex dynamic interactions between the cables and the marine environment.…”
Section: Introductionmentioning
confidence: 99%
“…The research highlighted the critical importance of accurate fatigue assessment in ensuring the reliability and longevity of power cables in FOWT applications. The power cable model in Sobhaniasl et al [36] was taken from Rentschler et al [37], who presented a novel approach for the design optimization of dynamic inter-array cable systems in floating offshore wind turbines. The study by Rentschler et al [37] was based on dynamic simulations of an OC4 FOWT with an attached dynamic power cable and employed a genetic algorithm to find the optimal distribution of buoyancy modules and optimal lazy wave geometry.…”
Section: Introductionmentioning
confidence: 99%